ANALYSIS OF THE EFFECT OF THE COVID-19 PANDEMIC ON AGRICULTURE SMALL AND MEDIUM ENTERPRISES IN KENYA - Makokha, Christabell D. (Tufts Archival Research Center, 2021)
Submitted in partial fulfillment of the degree Masters of International Business at the Fletcher School of Law and Diplomacy.; COVID-19 has affected all major industries globally, and we are seeing a shift in the way businesses operate in the wake of the pandemic disruptions. Small and medium enterprises (SMEs) in Africa are no exception. However, a year into the pandemic and beyond experts’ speculations, it is unclear how and to what extent these businesses have been affected. The goal of this research project was to gain an understanding of how SMEs in in the Agriculture Sector in Kenya have been affected by the COVID-19 pandemic; how they are coping with these stresses; and most importantly, identify the opportunities for these businesses to build back better, more resilient and robust operations.